Specialization in the bargaining family - Raphaela Hyee; Julio R. Robledo (Queen Mary University of London, Department of Economics, 2009)
We develop a two period family decision making model in which spouses bargain over their contributions to a family public good and the distribution of private consumption. In contrast to most models in the literature, specialization within the couple emerges endogenously from the production of the public good, and is not caused by exogenous differences between the spouses. Increasing marginal benefits of labour market experience make specialization efficient, even if both spouses have equal market and household productivities on the outset. If spouses are not able to enter into a binding contract governing the distribution of private consumption in the second period, the spouse specialized in market labour cannot commit to compensate the other spouse for foregone investments in earnings power. As a consequence, this spouse may withdraw part of his/her contribution and the provision level of the household good is likely to be inefficiently low.
Keywords: D19; H41; 330; family bargaining; specialization; private provision of public goods; Familienökonomik; Arbeitsteilung; Arbeitsangebot; Haushaltsproduktion; Verhandlungen; Scheidung; Theorie